Periodic table: a pedagogical proposal for elementary school (Research, Society and Development, 2020)
The article presents a pedagogical proposal involving a periodic table applied in classes of the ninth grade of elementary school, using varied didactic resources with playful characteristics and that allow an active participation of students, in order to facilitate the presentation of abstract and symbolic concepts of chemistry, favoring their understanding by the students. The activity was developed in two stages, with the first employing the stimulated memory technique to identify students' knowledge about the presence of chemical elements in their daily lives, involving their names, symbols and physical state, and the second presenting the periodic table a from the use of comic books and research activity. It involved a case study, with the form of data collection being the recording of classes, the production of material by students and the teacher's class diary. The activities were well accepted by the students, allowing the socialization of ideas and knowledge, with the active participation of the classes.